Desain Jaringan Sensor Nirkabel untuk Pemantauan Suhu Dan Kelembaban Lingkungan Berbasis SMS - Kostan D. F. Mataubenu; Muhammad Miftahul Munir (Saintek Lahan Kering, 2019)
Physical variables in everyday life that need to be monitored using a wireless sensor network are temperature and humidity. The advantages of using a wireless sensor network are to improve the resolution of the measurement data, to control remote application, to improve the efficiency, to control something in unreachable area and so on. Therefore, in this study a wireless sensor network were developed to monitor the temperature and humidity in environment based on short message system. The system was designed with a star topology consisted of two major parts, namely transmitter and the receiver. Transmitter consisted of XBee Pro RF module, microcontroller and sensor SHT10. Receiver consisted of XBee Pro RF modules that were connected with GSM module SIM900. Transmitters were placed on 3 points would send the measured data of temperature and humidity to the receiver, and then the data forwarded by short message system to destination phone number. The system has been tested and it works well.